PENGARUH LITERASI DIGITAL DAN AKSES TEKNOLOGI AKADEMIK TERHADAP MINAT BACA MAHASISWA DI PERPUSTAKAAN FKIP - Emelda Salsabila; Firman Firman; Ferdiaz Saudagar (Jurnal Manajemen Pendidikan, 2026)
Objective: Students’ reading interest in higher education remains a concern, despite the availability of various digital facilities and easier access to technology. This study aims to determine the influence of digital literacy and academic technology access on students’ reading interest at the Library of Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi. This research employed a quantitative approach using a survey method with a causal associative design. The population consisted of 4,885 sixth- and eighth-semester students, with a sample of 370 students selected through simple random sampling using the Slovin formula. Data were collected through observation, questionnaires, and documentation. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 through outer model and inner model testing. The results showed that digital literacy had a positive and significant effect on students’ reading interest, with a t-statistic value of 5.440 and a p-value of 0.000. Academic technology access also had a positive and significant effect on students’ reading interest, with a t-statistic value of 3.457 and a p-value of 0.001. Simultaneously, digital literacy and academic technology access influenced students’ reading interest with an R-Square value of 0.479, indicating that both variables explained 47.9% of students’ reading interest, while the remaining 52.1% was influenced by other factors outside this study.